The influence of perceived leadership behavior and psychological, empowerment on organizational commitment among secondary school teachers in Ampang, Selangor Darul Ehsan / Siti Mariam Hamid - Hamid, Siti Mariam (2014)
The purpose of this study was to investigate the influence of perceived leadership behavior and psychological empowerment on organizational commitment among secondary school teachers in Ampang. Six secondary schools in Ampang were selected for the study. The questionnaire was distributed to a total of 300 randomly selected teachers and 150 questionnaires were returned, however only 142 questionnaires were appropriately completed and able to be used for analysis. Data were analyzed using descriptive and inferential statistics. The findings revealed that the level of organizational commitment and its three components (affective commitment, continuance commitment and normative commitment) were at the moderate levels. The secondary school teachers perceived their principal and heads of department practicing transformational leadership. The levels of psychological empowerment and its four dimensions, namely autonomy, impact, professional growth and decision making, were at moderate level. However, the other dimensions of psychological empowerment, namely status and self-efficacy showed at high levels. The finding reveals organizational commitment was moderately and positively correlates to transformational leadership and psychological empowerment, but poses low and positive relationship with transactional leadership. Overall, the findings of this study have suggested teachers were highly committed and empowered when they perceived their principal and head of department practiced transformational leadership.